Modeling of Petrophysical Relationship of Soil Water Content Estimation at Peat lands - Abd Karim, Nurul Izzati; Kamaruddin, Samira Albati; Che Hasan, Rozaimi (International Journal of Integrated Engineering, 2018)
Estimating Soil Water Content (SWC) for peat soil is fundamental parameters that are essential for quality of soil especially during drying periods. Transformations and subsequent losses to groundwater or atmosphere are mediated by moisture conditions in the soil. Success or failure of food, fiber, and energy production from agricultural crops depends on soil water storage between rainfall and/or irrigation events. Despite this importance, predicting soil water dynamics especially during dry and wet season remains a major challenge in hydrology, environmental science, agriculture, and engineering. Hence this study aims to determine the mathematical model for the site-specific of petrophysical relationship for wet and dry season between dielectric permittivity and water content of the peat soil. Field survey measurements and laboratory measurements were conducted at peat soil area. Soil samples were collected from 0 to 1.0m layer for 20 point. Dielectric permittivity values were determined using 2D adjusted of parallel plate capacitor. The oven-drying process was conducted for soil water content estimation. Linear and polynomial models were adjusted for the peat soil between dielectric permittivity and water content. From the results shows that the modeled of site-specific of petrophysical relationship gives better correlation for dry season (R2=0.9812) and wet season (R2=0.9441). The comparisons of GPR-derived estimates of water content to gravimetric measurements showed that GPR measurements using the modeled site-specific petrophysical relationships for both season had a root mean square error of 0.017 (wet season) and 0.25 (dry season). This indicates that the modeled equations can be used to estimate the water content of the peat soil when measured it by using GPR. Besides, through verifying the model of site-specific of petrophysical relationship using ground penetrating radar (GPR) along with three proposed model (Roth equation, Schaap equation and Idi equation) where the season was taken as consideration, the adjusted models provide sufficient accuracy to determine soil water content of peat soil for wet and dry season.